Religion, spirituality and psychotic disorders (Archives of Clinical Psychiatry, 2007)
BACKGROUND: Religion is often included in the beliefs and experiences of psychotic patients, and therefore becomes the target of psychiatric interventions. OBJECTIVES: This article examines religious beliefs and activities among non-psychotic persons in the United States, Brazil and other areas of the world; discusses historical factors contributing to the wall of separation between religion and psychiatry today; reviews studies on the prevalence of religious delusions in patients with schizophrenia, bipolar disorder, and other severe mental disorders; discusses how clinicians can distinguish pathological from non-pathological religious involvement; explores how persons with severe mental illness use non-pathological religious beliefs to cope with their disorder; examines the effects of religious involvement on disease course, psychotic exacerbations, and hospitalization; and describes religious or spiritual interventions that may assist in treatment. METHODS: Literature review. FINDINGS: While about one-third of psychoses have religious delusions, not all religious experiences are psychotic. In fact, they may even have positive effects on the course of severe mental illness, forcing clinicians to make a decision on whether to treat religious beliefs and discourage religious experiences, or to support them. CONCLUSIONS: Clinicians should understand the negative and positive roles that religion plays in those with psychotic disorders.